Professores iniciantes e professores experientes : articulações possíveis para a formação e inserção na docência - Sousa, Rozilene de Morais (2015)
This research is linked to the UFMT Post Graduate Program in Education, in Rondonópolis’ Campus, with a project product approved in the Observatory of Education / 2013 entitled "Egress in Pedagogy and the Challenges of Narratives Practice: the University and the School in an interdisciplinary process of beginning teacher's inclusion in the teaching profession". The objective of this research consisted in analyzing the insertion of the beginning teacher in school, accompanied by an experienced teacher, investigating how the egress will constitute the teaching professional identity in the early years of the profession. It is settled in the qualitative approach, and anchoring in the method (auto) biographical, with the adoption of professional formation trajectory memorials and narrative interviews produced by five beginning teachers, three egress of the Federal University of Mato Grosso’s Pedagogy and two other of Higher Education Institutions’ Pedagogy, wherein act in public schools in Rondonópolis – MT. Even as subjects of this research was added two experienced teachers, which produced the formation memorials, focusing on the monitoring process of these beginners in the same educational institutions. Therefore, it was listed as research questions: What dilemmas and challenges the narratives of beginning teachers reported about the beginning of the teaching profession? What was narrated about the possibility of support from an experienced teacher who should assist the dilemmas and conflicts experienced in the first years of teaching? How was described their participation in the training processes propitiated by OBEDUC / 2013 project? How did it help in the process of constitution of teacher identity? The results of the data analyzed showed the main dilemmas and challenges of the egress in the process of integration in the school environment. It also highlighted the relevance and contributions of the monitoring of an experienced teacher in support in schools where the egress work. In addition, it showed the importance of the role of the OBEDUC research group in carrying out the formation of these beginners, minimizing their difficulties through a systematic and reflective monitoring of teaching and learning process developed in the school environment, thus contributing to the constitution of the teaching identity of the egress.